The Effectiveness of Artificial Intelligence in Enhancing Critical and Creative Thinking within the Pancasila Student Profile Framework - Harjanti, Fransisca Dwi; Suhartono, Suhartono; Ardiansyah, Roely; Suryandari, Savitri (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study examined how Artificial Intelligence (AI) applications influence the development of critical thinking and creativity within the Pancasila Student Profile framework in Indonesia. Using a quasi-experimental pre-test/post-test control design, the research involved 64 eleventh-grade students in a six-week project-based learning unit on environmental issues. The experimental group employed various AI tools, while the control group relied on conventional approaches. Students’ cognitive progress was assessed through validated essay tests and project rubrics. The results showed that AI integration led to substantially greater improvements in both critical thinking and creativity. Students in the AI-assisted group achieved significantly higher gains in critical thinking (5.63 vs. 2.18) and creativity (4.56 vs. 1.62), with large effect sizes indicating strong practical significance. These outcomes suggest that AI can function as a powerful cognitive amplifier, promoting deeper analytical thinking and more flexible idea generation. However, although AI enhanced cognitive aspects of the Pancasila Student Profile, it did not inherently support moral or social dimensions. Thus, future studies should investigate how AI can be combined with value-oriented and collaborative learning strategies to foster holistic development. Overall, the findings highlight the importance of adopting AI in balanced ways that advance higher-order thinking while upholding human-centered educational values.